Variability and predictability of finals times of elite rowers - Smith, T. B.; Hopkins, W. G. (Medicine & Science in Sports & Exercise, 2011)
Purpose: Little is known about the competitive performance characteristics of elite rowers. We report here analyses of performance times for finalists in world-class regattas from 1999 to 2009.